KUALITAS FISIK SUSU KAMBING PERAH YANG DISUPLEMENTASI DENGAN SOYBEAN MEAL (SBM) - Safira Huwaida; Muhtarudin Muhtarudin; Arif Qisthon; Liman Liman (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2022)
The study aimed to determine the effect of soybean meal supplementation in the ration on physical quality, namely specific gravity, pH, reductase, and dairy goat milk alcohol tests. The research was conducted from July to Agust 2021 at the Telaga Rizky Ranch owned by Mr. Setiono Heri Winarko, Yosodadi Village, East Metro District, Metro city. The samples used in this study were 12 Sapera goats that were lactating and grouped based on body weight. This study used a randomized block design (RBD) method with 4 treatments and 3 replication, namely P0 (control), P1 (soybean meal 5%), P2 (soybean meal 10%), P3 (soybean meal 15%). The data obtained were than analyzed by variance (ANOVA). The results showed that there was no significant effect (P>0.05) of the treatment on the physical test of diary goats’s milk supplemented with soybean meal. The result showed that the physical test of milk, namely for the specific gravity test was 1.0297 g/cm3, pH was 6,8, reductase was 8,0 hours, and alcohol test was negative. The physical quality of Sapera goat’s milk has good quality and is in accordance with the Indonesian Nasional Standard (2011). Keywords: alcohol, specific gravity, pH, reductase, soybean meal